Isoflavones Reduce Arterial Stiffness: A Placebo-Controlled Study in Men and Postmenopausal Women - Teede, Helena J.; McGrath, Barry P.; DeSilva, Lakmini; Cehun, Marja; Fassoulakis, Andriana; Nestel, Paul J. (Arteriosclerosis, thrombosis, and vascular biology, 2003)
OBJECTIVE—This study was undertaken to address the vascular effects of isolated isoflavones as potential contributors to their cardioprotective properties, focusing on biochanin and formononetin. METHODS AND RESULTS—In a randomized, double-blind trial, 80 healthy subjects, 46 men and 34 women, 45 to 75 years of age, received isoflavones enriched in either biochanin or formononetin (precursors of genistein and daidzein; 80 mg/d) crossed over randomly with placebo in two 6-week periods. The end points were measured at baseline and after each intervention and included large artery stiffness (systemic arterial compliance and pulse wave velocity), endothelial function in conduit arteries (flow-mediated vasodilation), 24-hour ambulatory blood pressure, and total peripheral resistance. Isoflavone intervention significantly reduced arterial stiffness with improved systemic arterial compliance (P =0.04; repeated-measures ANOVA, Bonferroni correction) attributable to a reduction in total peripheral resistance (P =0.03) and a corresponding reduction in central pulse wave velocity (P =0.02) compared with placebo. Isoflavones did not affect blood pressure (P =0.5) or flow-mediated vasodilation (P =0.44). Improvements seemed limited to formononetin-enriched isoflavones (adjusted P =0.06). Formononetin treatment also reduced circulating vascular adhesion cell molecule-1 (P <0.01). CONCLUSIONS—In normotensive men and postmenopausal women, red clover isoflavones enriched in formononetin reduced arterial stiffness and total vascular resistance but had no effect on blood pressure. These effects may partly explain the lower cardiovascular risk in populations eating isoflavone-rich diets.